A new front-tracking Lagrangian model for the modeling of dynamic and post-dynamic recrystallization. (8th March 2021) - Florez, Sebastian; Alvarado, Karen; Bernacki, Marc
Abstract: A new method for the simulation of evolving multi-domains problems has been introduced in previous works and further developed in parallel in the context of isotropic grain growth (GG) with no consideration for the effects of the stored energy (SE) due to dislocations. The methodology consists in a new front-tracking approach where one of the originality is that not only interfaces between grains are discretized but their bulks are also meshed and topological changes of the domains are driven by selective local remeshing operations performed on the finite element (FE) mesh. In this article, further developments and studies of the model will be presented, mainly on the development of a model taking into account grain boundary migration (GBM) by SE. Further developments for the nucleation of new grains will be presented, allowing to model dynamic recrystallization (DRX) and post-dynamic recrystallization (PDRX) phenomena. The accuracy and the performance of the numerical algorithms have been proven to be very promising in Florez et al (2020). Here the results for multiple test cases will be given in order to validate the accuracy of the model taking into account GG and SE. The computational performance will be evaluated for the DRX and PDRX mechanisms and compared to a classical FE framework using a level-set formulation.